Inferior Alveolar Nerve Injury after Mandibular Third Molar Extraction: a Literature Review - Rafael Sarikov; Gintaras Juodzbalys (Stilus Optimus, 2014)
Objectives: The purpose of this study was to systematically review the comprehensive overview of literature data about injury to the inferior alveolar nerve after lower third molar extraction to discover the prevalence of injury, the risk factors, recovery rates, and alternative methods of treatment. Material and Methods: Literature was selected through a search of PubMed electronic databases. Articles from January 2009 to June 2014 were searched. English language articles with a minimum of 6 months patient follow-up and injury analysis by patient's reporting, radiographic, and neurosensory testing were selected. Results: In total, 84 literature sources were reviewed, and 14 of the most relevant articles that are suitable to the criteria were selected. Articles were analyzed on men and women. The influence of lower third molar extraction (especially impacted) on the inferior alveolar nerve was clearly seen. Conclusions: The incidence of injury to the inferior alveolar nerve after lower third molar extraction was about 0.35 - 8.4%. The injury of the inferior alveolar nerve can be predicted by various radiological signs. There are few risk factors that may increase the risk of injury to the nerve such as patients over the age of 24 years old, with horizontal impactions, and extraction by trainee surgeons. Recovery is preferable and permanent injury is very rare.